Effect of intermittently scanned continuous glucose monitoring in people with diabetes with a psychosocial indication for initiation - Ssemmondo, Emmanuel; Deshmukh, Harshal; Wilmot, Emma G.; Adeleke, Kazeem A.; Shah, Najeeb; Walton, Chris; Barnes, Dennis; Ryder, Robert E.J.; Sathyapalan, Thozhukat (Diabetes, Obesity and Metabolism, 2024)
Aim: To understand the effect of intermittently scanned continuous glucose monitoring (isCGM) in people with diabetes with a ‘psychosocial’ indication for access. Methods: The study utilized baseline and follow-up data from the Association of British Clinical Diabetologists nationwide audit of people with diabetes in the UK. Diabetes-related distress (DRD) was assessed using the two-item diabetes-related distress scale (DDS). Participants were categorized into two groups: high DRD (DDS score ≥ 3) and lower DRD (DDS score < 3). The t-test was used to assess the difference in the pre- and post-isCGM continuous variables. Results: The study consisted of 17 036 people with diabetes, with 1314 (7%) using isCGM for ‘psychosocial’ reasons. Follow-up data were available for 327 participants, 322 (99%) of whom had type 1 diabetes with a median diabetes duration of 15 years; 75% (n = 241) had high levels of DRD. With the initiation of isCGM, after a mean follow-up period of 6.9 months, there was a significant reduction in DDS score; 4 at baseline versus 2.5 at follow-up (P <.001). The prevalence of high DRD reduced from 76% to 38% at follow-up (50% reduction in DRD, P <.001). There was also a significant reduction in HbA1c (78.5 mmol/mol [9.3%] at baseline vs. 66.5 mmol/mol [8.2%] at follow-up; P <.001). This group also experienced an 87% reduction in hospital admissions because of hyperglycaemia/diabetic ketoacidosis (P <.001). Conclusion: People with diabetes who had isCGM initiated for a psychosocial indication had high levels of DRD and HbA1c, which improved with the use of isCGM.
Keywords: Continuous glucose monitoring; Evidence; Glycaemic control; Real world; Type 1 diabetes